(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
The Charter of Fundamental Rights of the European Union has been applied directly by the Croatian Constitutional Court since the decision No. U-I-1397/2015 (Act on Elections of the Representatives to the Croatian Parliament) rendered in 2015. Ever since it can be observed that the Charter has been consistently applied both in the proceedings of constitutional review in abstracto and in the proceedings initiated by a constitutional complaint (constitutional review in concreto), however, in a limited number of cases mostly concerning migrations or asylum.Therefore, this paper analyses the application of the Charter in the case law of the Croatian Constitutional Court and the method of interpretation pursued, with special reference to both its shortcomings and benefits. The paper also investigates the reasons for limited application of the Charter, even in those cases which would normally fall under the scope of application of EU law. The analysis indicates two distinct methodological approaches adopted by the Constitutional Court. The first one, where the Charter has been regarded as an interpretative tool only; and the second one, where the Charter has been found to be directly applicable vis-à-vis individual rights inferred from the EU law. The latter approach, first followed in an asylum case No. U-III-424/2019 (X. Y.), had raised new questions on interpretation of the Charter (with respect to the Croatian constitutional framework) in the cases where the Charter’s applicability ratione materiae overlaps with the Croatian Constitution and the (European) Convention for the Protection of Human Rights and Fundamental Freedoms, which to the day, in contrast to the Charter, has been consistently followed and therefore legally internalised by the Croatian Constitutional Court. Therefore, the paper also elaborates a new methodological approach adopted by the Croatian Constitutional Court in finding a way out of „limbo“ between the Charter, the ECHR, and the Croatian Constitution.